Removal of fluoride ion from aqueous solution by a Cerium-poly(hydroxamic acid) resin complex - Haron, M.J.; Wan Yunus, W.M.Z. (Taylor & Francis, 2001)
A cerium-loaded poly(hydroxamic acid) chelating ion exchanger was used for fluoride ion removal from aqueous solution. The resin was effective in decreasing the fluoride concentration from 5 mM down to 0.001 mM in acidic pH between 3 and 6. The sorption followed a Langmuir model with a maximum capacity of 0.5 mmol/g. The removal is accomplished by an anion exchange mechanism. The rate constant for the sorption was found to be 9.6 × 10-2min-1. A column test shows that the fluoride ion was retained on the column until breakthrough point and the fluoride sorbed in the column can be eluted with 0.1 M NaOH. The column can be reused after being condition with hydrochloric acid at pH 4. The resin was tested and found to be effective for removal of fluoride from actual industrial wastewater.